New Developments in Prokinetic Therapy for Gastric Motility Disorders - Michael Camilleri; Jessica Atieh (Frontiers Media S.A., 2021)
Prokinetic agents amplify and coordinate the gastrointestinal muscular contractions to facilitate the transit of intra-luminal content. Following the institution of dietary recommendations, prokinetics are the first medications whose goal is to improve gastric emptying and relieve symptoms of gastroparesis. The recommended use of metoclopramide, the only currently approved medication for gastroparesis in the United States, is for a duration of less than 3 months, due to the risk of reversible or irreversible extrapyramidal tremors. Domperidone, a dopamine D2 receptor antagonist, is available for prescription through the FDA's program for Expanded Access to Investigational Drugs. Macrolides are used off label and are associated with tachyphylaxis and variable duration of efficacy. Aprepitant relieves some symptoms of gastroparesis. There are newer agents in the pipeline targeting diverse gastric (fundic, antral and pyloric) motor functions, including novel serotonergic 5-HT4 agonists, dopaminergic D2/3 antagonists, neurokinin NK1 antagonists, and ghrelin agonist. Novel targets with potential to improve gastric motor functions include the pylorus, macrophage/inflammatory function, oxidative stress, and neurogenesis. In the current review, we discuss the use of pharmacological approaches with potential to enhance motor functions in the management of gastroparesis.